The Impact of Economic Value Added Index on the Components of Companies Financing Structure - An Applied Study - Alhassan, Omer Alsir; Alhassan, Abdalgader Idrees (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to explain the impact of economic value added indicator on components of companies’ financing structure in Sudanese Communication Company (Sudatel)2008-2017. By examining the statistical analysis of the study found that the Sudanese companies showed weak interest in the economic value indicator as modern for evaluation of performance since the most studies focused on the traditional indicators. They found also a statistical significant effect of the economic value added indicator on the evaluation of self-financing in Sudanese Communication Company (Sudatel) as well a statistical significant effect of the economic value added indicator on the evaluation of non-self financing in Sudanese Communication Company (Sudatel). The study recommended that more attention should be paid to the economic value added indicator beside the traditional indicators at the evaluation of companies’ performance, and comparison should be made between the modern financial indicators and traditional financial indicators at judging companies’ financial performance.
Keywords: added economic value; self-financing; financing structure